KONTRIBUSI PONDOK PESANTREN TERHADAP PERUBAHAN SOSIAL MASYARAKAT DI PULAU BANGKA (Studi Pondok Pesantren Al-Islam Desa Kemuja Kecamatan Mendo Barat Kabupaten Bangka) (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2020)
The purpose of this study is to determine how the contribution of Islamic boarding schools to the social change in society so that it has a positive influence on the growth of the times, socially and culture. From the author's observations, the background is that Islamic boarding schools in Indonesia are one of the most important educational institutions so that they can direct more advanced pesantren education. The presence of Islamic boarding schools in the midst of this community also provides various styles for the surrounding community. Because at the beginning of the pesantren it was supported by the community, so changes that occur in society will also involve the existence of the pesantren. The results of this research study conclude that there are several contributions of pondok rapidly to social change, namely: education and teaching, ubudiyah and religion and muamalah and social fields. Meanwhile, the pesantren's efforts in building social change in society are through: majlis ta'lim, ramadhan safaris, mass circumcision, and tabliqh akbar.